Melalui Pendekatan Saintififik Model Pembelajaran Covid-19 Metode Blanded Learning untuk Meningkatkan Hasil Belajar Peserta Didik Muatan Pembelajaran IPS Tema Persatuan dalam Perbedaan di Kelas VI SD Negeri 60 Payakumbuh Semester Ganjil Tahun Pelajaran - Isnamila Marhayati (Departement of Mathematics Education, 2022)
This study aims to analyze Improving Social Studies Learning Outcomes with the Theme of Unity in Diversity through the Scientific Approach of the Covid-19 Model with the Blended Learning method in grade VI SD Negeri 60 Payakumbuh. This research was carried out using the Classroom Action Research method which consisted of two cycles, where each cycle consisted of planning, action, reflection, and evaluation which was carried out from July to September 2021. The data was processed in each cycle and then analyzed using percentages. The results obtained from this study are the scientific approach of the Blended Learning Model can improve student learning outcomes. This is evident from the learning outcomes obtained for the knowledge aspect, which increased from 66.76 in pre-cycle activities to 73.53 in the first cycle, increasing again to 88.82 in the second cycle with a percentage increase of 22.06%. The learning outcomes of the skills aspect obtained an average of 69.41 in the pre-cycle, increasing to 77.65 in the first cycle and increasing again to 92.35 in the second cycle with a percentage increase of 22.94%. The conclusion obtained from this study is that the use of a scientific approach to the Blended Learning Model can improve student learning outcomes